Single-molecule profiling of per- and polyfluoroalkyl substances by cyclodextrin mediated host-guest interactions within a biological nanopore - Wei, Xiaojun (2024)
Biological nanopores are increasingly used in molecular sensing due to their single-molecule sensitivity. Thedetection of per- and polyfluoroalkyl substances (PFAS) like perfluorooctanoic acid and perfluorooctane sulfonicacid is critical due to their environmental prevalence and toxicity. Here, we investigate selective interactionsbetween PFAS and four cyclodextrin (CD) variants (α- , β- , γ- , and 2- hydroxypropyl- γ-CD) within an α- hemolysinnanopore. We demonstrate that PFAS molecules can be electrochemically sensed by interacting with a γ-CD in ananopore. Using HP-γ- CDs with increased steric resistance, we can identify homologs of the perfluoroalkylcarboxylic acid and the perfluoroalkyl sulfonic acid families and detect common PFAS in drinking water at 0.4 to2 parts per million levels, which are further lowered to 400 parts per trillion by sample preconcentration. Moleculardynamics simulations reveal the underlying chemical mechanism of PFAS-CD interactions. These insights pave theway toward nanopore-based in situ detection with promises in environmental protection against PFAS pollution.